2017
DOI: 10.24953/turkjped.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

High frequency oscillatory ventilation versus conventional mechanical ventilation in pediatric acute respiratory distress syndrome: A randomized controlled study

Abstract: Although the HFO mode appeared to be a safe mode with a significant better oxygenation improvement (after the first 24 hours) and fewer crossover rates, it failed to show differences as regards mortality or LOS when compared to the CMV adopting protective lung strategy. In PARDS, HFO had a superior advantage in improving oxygenation, yet with no significant mortality improvement, as multi-organ dysfunction syndrome (MODS) was the most common cause of death in our study and not refractory hypoxemia which is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 61 publications
1
23
0
5
Order By: Relevance
“…45 More recently, a Turkish RCT of 200 children with PARDS found that HFOV improved oxygenation but showed no difference in mortality, duration of mechanical ventilation, or length of stay (LOS), compared to CMV. 29 Consistent with other studies, the most common cause of death was multiorgan dysfunction rather than refractory hypoxemia. A metaanalysis of 6 RCTs with a total of 246 PARDS patients also demonstrated improved oxygenation with no significant difference in mortality or duration of mechanical ventilation.…”
Section: High-frequency Ventilationsupporting
confidence: 88%
See 2 more Smart Citations
“…45 More recently, a Turkish RCT of 200 children with PARDS found that HFOV improved oxygenation but showed no difference in mortality, duration of mechanical ventilation, or length of stay (LOS), compared to CMV. 29 Consistent with other studies, the most common cause of death was multiorgan dysfunction rather than refractory hypoxemia. A metaanalysis of 6 RCTs with a total of 246 PARDS patients also demonstrated improved oxygenation with no significant difference in mortality or duration of mechanical ventilation.…”
Section: High-frequency Ventilationsupporting
confidence: 88%
“…Cheifetz, 20 El-Nawawy et al, 29 Ferguson et al, 41 Young et al, 42 Arnold et al, 43 Gupta et al, 44 Bateman et al, 45 Qiao et al 46 Prone positioning 50% Mortality reduction in severe ARDS (single RCT). Adult systematic reviews report improved oxygenation, safe, potential mortality reduction when coupled with other lung protective strategies.…”
Section: Rimensberger Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Dos 307 ensaios clínicos randomizados identificados nas bases de dados, nove (n = 9) cumpriram os critérios e foram incluídos para a composição desta revisão. Fluxograma descrevendo as fases da pesquisa está representado na Figura 1. No que se refere à aplicabilidade da VOAF, a maior parte dos estudos incluídos discorre sobre a comparação dessa modalidade ventilatória à ventilação mecânica convencional 11,12,13,15,16 . Os principais desfechos utilizados foram a ocorrência de displasia broncopulmonar, retinopatia da prematuridade, hemorragia peri-intraventricular, variáveis gasométricas, tempo de ventilação mecânica invasiva, mortalidade e variáveis de oxigenação, em diversas condições clínicas.…”
Section: Resultsunclassified
“…It is known that most patients with ARDS do not die due to severe hypoxemia but due to sequential organ function failure (SOFA) [21]. The SOFA score is an independent risk factor predicting death in ARDS [22].…”
Section: Discussionmentioning
confidence: 99%